Illegal occupations of public buildings. As legitimate cohabitation models - Chiara Tonelli; Ilaria Montella (Agathón)
Economic crises, continuous migration and insufficient social housing responses are leading an ever-widening segment of the population towards a housing emergency. Due to the lack of institutional or affordable solutions, squatting becomes the only option that is both viable and immediate. Informal occupations, although time-limited, are an answer to satisfy the primary housing need. In studying the patterns used in these urgent situations, the authors consider the emergence of organisational and design models that can facilitate defining a new residential legislation. This contribution illustrates the case study of Spin Time Labs. Located in an occupied public building in Rome’s historical centre, Spin Time Labs is a temporary cohabitation model and an urban regeneration catalyst.